1974
DOI: 10.1111/j.1600-0609.1974.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Features of the Granulocytes in Down's Syndrome

Abstract: The granulocytes of 9 patients with Down's syndrome (DS) were examined for morphological abnormalities. Electron microscope examination showed abnormalities in the nucleus, such as pockets, bridges, appendices and fibrillar bodies in 25–57 % of the cells as compared to similar, but less conspicuous findings in 5–10 % of the granulocytes of 5 controls. The similarity of these ultrastructural malformations to those described in different forms of leukaemia is stressed. Since chromosomal abnormalities exist in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The morphological alterations of the granulocytes in the case presented are similar to those observed in Down's syndrome (Djaldetti et al 1974) and in different forms of leukemia. Moreover, the development of leukemia in this patient raises the question of a possible connection between ultrastructural abnormalities in the granulocytes and the development of leukemia.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The morphological alterations of the granulocytes in the case presented are similar to those observed in Down's syndrome (Djaldetti et al 1974) and in different forms of leukemia. Moreover, the development of leukemia in this patient raises the question of a possible connection between ultrastructural abnormalities in the granulocytes and the development of leukemia.…”
Section: Discussionsupporting
confidence: 80%
“…They claimed that the observed nuclear abnormalities are specific for this disease. Djaldetti et al (1974) observed similar abnormalities in granulocytes of nine patients with Down's syndrome. The authors drew attention to the similarity between these ultrastructural malformations and those described in the white blood cells in different forms of leukemia (Anderson 1966, Fujinaga 1966 Ahearn et al 1967, Besses 1968, Freeman & Journey 1971, Djaldetti et at.…”
Section: Discussionmentioning
confidence: 54%
“…Fanconi's anemia granulocytes Barton et al 1987 Acquired sideroblastic anemia granulocytes Djaldetti et al 2004 Megaloblastic anemia (B12 deficiency) granulocytes Bunting and Selig 2002;Bunting et al 1996 Congenital dyserythropoietic anemia (CDA) erythrocyte precursors Bjorksten et al 1978 Chromosomal aneuploidy D 1 (13-15) trisomy granulocytes Fine et al 1965;Huehns et al 1964;Lutzner and Hecht 1966;Mehes 1966;Rogers 1984;Salama et al 2004 14 trisomy granulocytes Dallapiccola et al 1984 21 Trisomy (Down's Syndrome) granulocytes Djaldetti et al 1974;Gericke et al 1977 Various combinations of aneuploidy, translocations and inversions granulocytes Ahearn et al 1974;Dalton et al 1987;Tricot and Broeckaert-Van Orshoven 1984 Chemotherapy/mitotic agents 5-Fluorouracil granulocytes Stalzer et al 1965 Cytosine arabinoside granulocytes Ahearn et al 1967 Mitotic inhibitor SK & F Burkitt's lymphoma cells Erenpreisa et al 2002 Phytohemagglutinin Blood mononuclear cells Mollo and Stramignoni 1967 Sodium periodate CLL cells McGill et al 1976 Cytochalasin B and concanavalin A lymphocytes Viklicky et al 1978 B12 deficiency), which is thought to provoke a perturbation of DNA replication in the bone marrow (Bunting and Selig 2002;Bunting et al 1996). It may be that the common feature of these cell cycle insults is the induction of a "mitotic crisis" (Erenpreisa et al 2002).…”
Section: Lymphomamentioning
confidence: 97%